The Comparative Study Of Randomness Analysis Between Modified Version Of LBlock Block Cipher And Its Original Design - Nik Azura Nik Abdullah; Liyana Chew Nizam Chew; Abdul Alif Zakaria; Kamaruzzaman Seman; Norita Md Norwawi (International Journal of Computer and Information Technology, 2024)
Volume 04 Issue 06 (page:867-875)